Variasi Genetika Kelelawar Genus Aethalops (Chiroptera: Pteropodidae) di Indonesia: Tinjauan dari Gen 12SrRNA pada DNA Mitokondria - Maharadatunkamsi, Maharadatunkamsi; Zein, M. Syamsul Arifin (JURNAL BIOLOGI INDONESIA, 2006)
ABSTRACTGenetic Variation of Bat in the Genus Aethalops (Chiroptera: Pteropodidae) fromIndonesia: Analysis of 12SrRNA Gene of Mitochondria1 DNA. We report a geneticvariation on 12SrRNA gene to investigate haplotype and nucleotide diversity, as well aspopulation structure of bats in the genus Aethalops. Samples consisted of 21 individualsfrom 7 populations of 5 islands (Sumatra, Jawa, Kalimantan, Bali and Lombok) coveringall islands distribution of this genus in Indonesia. Total DNA was extracted from livertissues. Fragment 12SrRNA gene region of the mitochondria1 DNA were amplified byPolymerase Chain Reaction usingprimers of L 1091 and H 1478. Nucleotide sequenceswere determined to investigate genetic variation of this genus. Results indicated thatfrom 294 bp nucleotide sequences, 33 polymorphic sites with 13 haplotypes were foundamong 7 populations.Key Words: Variation, Bat, Aethalops , Chiroptera, Indonesia, 12SrRNAmitochondrial.